Evaluation of the Workload of PPSDM Migas Refinery Operators on Organizational Effectiveness and Efficiency - Virgiawan Surya Pradana; Muhammad Nur Abdi (Citakonsultindo, 2025)
This study evaluates the workload of refinery operators at PPSDM Migas and its impact on organizational effectiveness and efficiency using a descriptive qualitative with 8 key informants approach. Interviews show that operators handle a high and varied task load, including equipment operation, inspections, reporting, coordination, and troubleshooting especially during start-up, shutdown, and unstable operating conditions. The 3-team shift system, particularly night shifts, increases physical and mental strain due to reduced rest and the need for heightened alertness. Operators generally perceive the workload as heavy, driven by high responsibility and operational risks. Excessive workload contributes to increased human error, reduced vigilance, potential emergency shutdowns, and lower productivity. However, regular training and certification help enhance operator competence and support stable operations. Overall, the findings highlight that effective workload management through adequate staffing, improved shift arrangements, digitalized monitoring, and strengthened competencies is essential for maintaining organizational effectiveness and efficiency in refinery operations.